INTEGRATED MARKETING COMMUNICATION: HOW IMC METHOD BUILD A BRAND EQUITY: KOMUNIKASI PEMASARAN TERPADU: BAGAIMANA METODE IMC MEMBANGUN EKUITAS MEREK - Andi Nurul Habibah; Fany Mulyono; Ce Gunawan (Marketgram Journal, 2023)
Facing increasingly competitive competition, companies are required to be more innovative to developing the corporate image of the products that will be created in order to compete with competitors. In this literature it will be known that every form of marketing communication activity will always aim to contribute to brand equity and drive sales. To produce effective communication, it takes more than just marketing communication tools that have been used so far. This concept became the idea for creating a marketing strategy known as IMC (Integrated Marketing Communication). This literature will also explain how much influence the use of the right IMC strategy and variant has on the effectiveness of the message conveyed in increasing a company's brand equity. Because for companies, high brand equity will provide competitive advantage.